The connection between Trypanosoma cruzi transmission cycles by Triatoma brasiliensis brasiliensis: A threat to human health in an area susceptible to desertification in the Seridó, Rio Grande do Norte, Brazil. - Vanessa Lima-Neiva; Helena Keiko Toma; Lúcia Maria Abrantes Aguiar; Catarina Macedo Lopes; Letícia Paschoaletto Dias; Teresa Cristina Monte Gonçalves; Jane Costa (Public Library of Science (PLoS), 2021)
An outbreak of Chagas disease, possibly involving its vector Triatoma brasiliensis brasiliensis, was identified in the state of Rio Grande do Norte (RN). Given the historical significance of this vector in public health, the study aimed to evaluate its role in the transmission dynamics of the protozoan Trypanosoma cruzi in an area undergoing desertification in the Seridó region, RN, Brazil. We captured triatomines in sylvatic and anthropic ecotopes. Natural vector infection was determined using parasitological and molecular methods and we identified discrete typing units (DTUs) of T. cruzi by analyzing the COII gene of mtDNA, 24Sα rDNA, and mini-exon gene. Their blood meals sources were identified by amplification and sequencing of the mtDNA cytochrome b gene. A total of 952 T. b. brasiliensis were captured in peridomestic (69.9%) and sylvatic ecotopes (30.4%). A wide range of natural infection rates were observed in peridomestic (36.0% - 71.1%) and sylvatic populations (28.6% - 100.0%). We observed the circulation of TcI and TcII DTUs with a predominance of Tcl in sylvatic and peridomestic environments. Kerodon rupestris, rocky cavy (13/39), Homo sapiens, human (8/39), and Bos taurus, ox (6/39) were the most frequently detected blood meals sources. Thus, Triatoma b. brasiliensis is invading and colonizing the human dwellings. Furthermore, high levels of natural infection, coupled with the detection of TcI and TcII DTUs, and also the detection of K. rupestris and H. sapiens as blood meals sources of infected T. b. brasiliensis indicate a risk of T. cruzi transmission to human populations in areas undergoing desertification.